Quantum Computing Applications in Software Engineering: A Scoping Review - Hillary T. OGBODO; Bilkisu L. MUHAMMAD-BELLO; Joshua ABAH; Saleh E.-Y. ABDULLAHI (FUDMA Journal of Engineering and Technology, 2026)
The emerging field of quantum computing (QC) uses principles of quantum mechanics, such as superposition and entanglement, to deliver powerful computing capabilities. Through these principles, qubits can exist in a combination of states at the same time, enabling quantum computers to solve complex problems that classical computers cannot. QC promises to be useful for many important tasks in software engineering at different stages of the SDLC. The Software Engineering (SE) field is only beginning to integrate QC practices, and this integration is still at an early stage. This study is a scoping review that investigates the application of QC in SE to understand the techniques, trends, practices, and gaps. Based on the framework developed by Arksey and O’Malley, five databases were screened, yielding 180 initial records. After screening, 20 studies from 2020 to 2025 were identified, consisting of 14 primary studies and 6 secondary works (three SLRs, two surveys, and an edited book), which were kept as contextual references. The results show that testing and operations were largely optimized using quantum-inspired algorithms, while software architecture, economics, and security received less attention. The review also provides a future research platform for quantum software engineering (QSE).